ENGLISH LANGUAGE TEACHING CHALLENGES IN STATE VOCATIONAL HIGH SCHOOLS IN SURABAYA (RETAIN, 2015)
Abstract The aim of this study is to investigate the challenges faced by English teachers in their English Language Teaching in state vocational high schools in Surabaya and whether any significant differences in response of the challenges among them based on their ages, education level and teaching workload per week. This study was conducted in 10 state vocational high schools in Surabaya which involved 69 English Teachers. This study used survey research as the research design. SPSS. 20 was employed in the study as the tool for analyzing the data from the questionnaires to answer all the research questions. The findings of the study show that teaching challenges included the difficulty to transfer English knowledge to their students, mismatch situation between the student’s lack of English proficiency and high-stake curriculum, inadequacy of language laboratory to support ELT, and the English teachers also have too much workload. There was no significant difference in responses the English Language Teaching challenges among English teachers based on their age, level of education, and teaching workload. It can be concluded that the ESP teaching challenges in previous study (which conducted by Marwan in 2009) also present in this study, in other words the English Teachers in state vocational high schools in Surabaya also voice the same challenges in their English Language teaching and only factor of English Teachers’ teaching workload differs in response the challenge which probably caused by fatigue in their teaching. Keywords: English Language Teaching, ESP, English Teachers, State Vocational High Schools, Challenge Abstrak Studi ini bertujuan untuk meneliti tantangan-tantangan yang dihadapi oleh guru bahasa inggris dalam mengajar bahasa inggris di sekolah menengah kejuruan negeri di Surabaya dan jika ada perbedaan signifikan dalam merespon tantangan-tantangan tersebut berdasarkan usia, tingkat pendidikan, dan jam mengajar per minggu. Studi ini diadakan di 10 sekolah menengah kejuruan negeri di Surabaya yang melibatkan 69 guru bahasa inggris. Studi ini menggunakan penelitian survey sebagai desain penelitian. SPSS. 20 digunakan sebagai alat untuk menganalisa data dari angket untuk menjawab semua pertanyaan penelitian. Hasil dari studi ini menunjukkan bahwa adanya tantangan kesulitan dalam mentransfer pengetahuan bahasa inggris kepada peserta didik mereka, ketidaksesuaian antara kurangnya pengalaman dan kemampuan bahasa inggris peserta didik (kenyataan) dengan tuntutan kurikulum yang tinggi, laboratorium bahasa yang tidak mendukung kegiatan English Language Teaching, beban kerja terlalu banyak. Tidak ada perbedaan yang signifikan dalam merespon tantangan-tantangan dalam English Language Teaching diantara guru-guru bahasa inggrs berdasarkan usia, tingkat pendidikan, dan beban mengajar tiap minggu di sekolah menengah kejuruan negeri di Surabaya. Dari hasil yang ditemukan, dapat disimpulkan bahwa tantangan mengajar ESP di studi sebelumnya (yang dilakukan oleh Marwan pada tahun 2009) juga terdapat di studi ini, yang berarti bahwa guru bahasa inggris di sekolah menengah kejuruan negeri di Surabaya juga menyuarakan tantangan English Language Teaching yang sama dan hanya faktor beban mengajar per minggu guru bahasa inggris yang membedakan respon terhadap tantangan yang kemungkinan disebabkan oleh kelelahan dalam mengajar. Kata Kunci: English Language Teaching, ESP, Guru Bahasa Inggris, Sekolah Menengah Kejuruan Negeri, Tantangan